2018
DOI: 10.3324/haematol.2018.196279
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death protein-1 (PD-1)-expression in the microenvironment of classical Hodgkin lymphoma at relapse during anti-PD-1-treatment

Abstract: Inhibition of the immunoregulatory programmed cell death-protein-1 (PD-1)/PD-ligand (PD-L)-pathway by PD-1 blocking antibodies has resulted in high response rates in patients with relapsed/refractory (r/r) classical Hodgkin lymphoma (cHL). Nevertheless, the majority of r/r cHL patients relapse on anti-PD-1 treatment. To address the unsolved question of mechanisms of resistance to anti-PD-1 blockade in cHL we retrospectively examined sequential biopsies of nine r/r cHL-patients with progressive disease or relap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 13 publications
1
24
0
1
Order By: Relevance
“…We read with interest the recent paper published in Haematologica by Sasse et al examining programmed cell death protein -1 (PD1) expression in paired pretreatment/relapse samples for patients receiving PD1 inhibitor therapy in classical Hodgkin lymphoma (CHL). 1 Although the authors comment on an increase in PD1 + lymphocyte numbers in cases relapsing after PD1 inhibitor therapy, this difference did not reach statistical significance. The possibility that PD1 + lymphocytes might be enriched post PD1 inhibitor therapy is interesting, and raises a number of questions.…”
mentioning
confidence: 95%
“…We read with interest the recent paper published in Haematologica by Sasse et al examining programmed cell death protein -1 (PD1) expression in paired pretreatment/relapse samples for patients receiving PD1 inhibitor therapy in classical Hodgkin lymphoma (CHL). 1 Although the authors comment on an increase in PD1 + lymphocyte numbers in cases relapsing after PD1 inhibitor therapy, this difference did not reach statistical significance. The possibility that PD1 + lymphocytes might be enriched post PD1 inhibitor therapy is interesting, and raises a number of questions.…”
mentioning
confidence: 95%
“…Finally, spatial organization of cell types in combination with their abundance has been shown to provide relevant insight into the interaction between HRSC and the microenvironment in vivo [29]. Of note, our method of immunohistochemistry in fact is able to detect variability in PD1 expression as we have shown recently in patients suffering from a relapse after anti-PD1 treatment [12].…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, it is currently not known whether therapeutic targets like PD-L1/ PD1 and CD30 change under conventional chemotherapy and which biopsies need to be assessed if the status should be assessed for targeted treatment at relapse. In fact, we recently showed that the number of PD1-positive cells increased in patients relapsing after/under anti-PD1 treatment [12]. We thus analyzed multiple biopsy specimens from cHL patients and compared histological subtype, immunophenotype, and microenvironment at diagnosis and at relapse to understand which tissue needs to be analyzed when assessing the presence of therapeutic targets CD30, PD1, and PD-L1 or prognostic biomarker such as the macrophage content in cHL.…”
Section: Introductionmentioning
confidence: 99%
“…[349][350][351][352] In addition, checkpoint inhibitors combined with CAR-T therapy, epigenetic modulators, radiotherapy, and BTK inhibitors have shown striking efficacy in refractory lymphoma. [353][354][355] PD-1/PD-L1 Programmed cell death-1 (PD-1, also known as CD279) is a member of the immunoglobulin superfamily and functions as an important immune checkpoint that suppresses excessive immune responses. 6 PD-1 is mainly expressed on activated T cells and a small number of B cells, NK cells, activated monocytes, and dendritic cells but is not expressed on naïve T cells.…”
Section: Tumor Microenvironment and Checkpoint-related Targeted Therapymentioning
confidence: 99%